Effect of filler metal feed rate and composition on microstructure and mechanical properties of fibre laser welded AA 2024-T3. (January 2017) - Ahn, J.; Chen, L.; He, E.; Davies, C.M.; Dear, J.P.
Abstract: The influence of aluminium alloy 4043 filler wire feed rate on the weld quality and mechanical properties of high power 5 kW fibre laser welded aluminium alloy 2024-T3 was investigated. Loss of volatile alloying elements such as magnesium and other elements including copper and silicon which all contributed to the hot crack sensitivity was measured using energy dispersive X-ray spectroscopy at different filler wire feed rates. High feed rates of above 4.0 m/min produced instabilities, whereas, low feed rates below 2.0 m/min did not sufficiently modify the chemical composition of the weld pool. The optimum feed rate was found to be in the range between 2 and 3 m/min, where the corresponding dilution ratio of around 9–12% in the weld pool with less than 0.6% silicon content reduced the percentage of Mg2 Si and also decreased the solidification temperature and total shrinkage during freezing. The addition of filler metal reduced the risk of welding defects and improved ductility to over 3.5% and a fairly higher tensile strength of around 380 MPa than without. Microstructural examination showed that the addition of filler wire increased the number of finer dimples within the weld, resulting in a purely ductile fracture behaviour, as well as reduced micro hot cracks and porosities.